A Poultry Value Chain Intervention Promoting Diversified Diets Has Limited Impact on Maternal and Child Diet Adequacy during the Lean Season in a Cluster Randomized Controlled Trial. Issue 5 (16th February 2022) - Becquey, Elodie; Diop, Loty; Awonon, Josue; Diatta, Ampa D; Ganaba, Rasmane; Pedehombga, Abdoulaye; Gelli, Aulo
ABSTRACT: Background: Soutenir l'Exploitation Familiale pour Lancer l'Élevage des Volailles et Valoriser l'Économie Rurale (SELEVER) is a nutrition- and gender-sensitive poultry value chain project designed and implemented by international nongovernmental organization Tanager, which consists of poultry market facilitation and behavior change activities aiming at increasing poultry production and improving diets without free inputs transfer. Objectives: The study aimed at assessing the impact of SELEVER on diets of women and children during the lean season. Methods: Within a cluster randomized controlled trial, 45 communes were assigned to 1 of 3 arms, including 1 ) SELEVER interventions, 2 ) SELEVER with an intensive hygiene and sanitation component (SELEVER + WASH), and 3 ) a control group without intervention. Two rounds of survey were conducted 2 y apart during the lean season. Primary dietary outcomes were the probability of adequacy (PA) of iron, zinc, and vitamin A intakes; mean PA of 11 micronutrients and individual dietary diversity score collected through quantitative 24-h recall in longitudinal samples of women and index children (2–4 y old) in 1054 households; and minimum acceptable diet in the repeated cross-sectional sample of their younger sibling aged 6–23 mo. Impacts were assessed by intention-to-treat ANCOVA. Results: Relative to control, SELEVER interventions (groups 1 + 2) increased the PA of iron intakes in women by 1.8 percentage points (pp) ( P = 0.030). We found no further impact on primary outcomes, although egg consumption increased in index children (+0.73 pp, P = 0.010; +0.69 kcal/d, P = 0.036). Across the 3 groups, we observed negative effects of SELEVER on the PA of zinc intakes in women relative to SELEVER + WASH (–4.1 pp, P = 0.038) and on a variety of secondary dietary outcomes relative to both other groups. The study was registered on the ISCRCTN registry (ISRCTN16686478). Conclusions: Information-only-based value chain interventions may not have meaningful positive effects on diets of women and children in the lean season in settings with largely inadequate diets. We found suggestive evidence that synergies between intervention components may have introduced heterogeneity in effects on diet.